SHIFT WORK AND THE HEART: EFFECTS OF SHIFT WORK ON THE DEVELOPMENT AND PROGRESSION OF HEART FAILURE AND ITS ASSOCIATION WITH CHRONIC DISEASE RISKS - A NARRATIVE REVIEW - Natalia Nawrocka; Filip Bednarek; Olga Plinta; Alicja Hojda; Hanna Rodak; Izabela Małajewicz; Małgorzata Pietrzyk; Dawid Stępień; Karolina Oskroba; Igor Kłak (International Journal of Innovative Technologies in Social Science, 2026)
Background: Shift work is increasingly prevalent worldwide as continuous service delivery becomes essential across sectors such as healthcare, transportation and industry. However circadian misalignment, sleep disruption, metabolic alterations and neurohormonal dysregulation make shift workers a population at heightened cardiometabolic risk. While the associations between shift work, hypertension and coronary artery disease (CAD) are well documented, its potential contribution to the development of heart failure (HF) remains less clearly defined. Objectives: This narrative review synthesises current evidence on the impact of shift work - particularly night work and rotating schedules - on cardiovascular health with a focus on HF, CAD and hypertension. It contextualises HF risk within the broader metabolic and behavioural consequences of circadian disruption and identifies gaps in existing research. Methods: A comprehensive review of epidemiological, clinical and experimental studies was conducted with emphasis on cardiometabolic pathways linking shift work to adverse cardiovascular outcomes. Results: Shift work is consistently associated with an increased risk of hypertension and CAD with risk rising in proportion to cumulative exposure. Pathophysiology includes chronic sympathetic activation, inflammation, oxidative stress, hormonal dysregulation and frequent co-occurrence of unhealthy sleep, dietary and activity patterns. Evidence linking shift work to HF is more limited but suggests an elevated risk - particularly among women and permanent night-shift workers. Proposed mechanisms include chronic haemodynamic stress, myocardial fibrosis (supported by experimental models) and indirect effects mediated by worsened metabolic health. Heterogeneity in exposure definitions and inadequate adjustment for confounders remain key limitations of existing studies. Conclusions: Shift work should be considered as an important, modifiable cardiovascular risk factor that may contribute not only to hypertension and CAD but also to HF development. Preventive strategies - including optimisation of shift schedules, adequate recovery periods and education targeting sleep hygiene, diet and physical activity - may mitigate these risks. Well-designed prospective studies with HF as a primary endpoint, detailed exposure assessment and phenotype-specific analyses are urgently needed. Greater awareness of the cardiovascular consequences of shift work is essential for clinicians, employers and public health policymakers.